Clinical and Practice Variations in Pediatric Acute Recurrent or Chronic Pancreatitis: Report From the INSPPIRE Study. Issue 1 (July 2020) - Dike, Chinenye R.; Zimmerman, Bridget; Zheng, Yuhua; Wilschanski, Michael; Werlin, Steven L.; Troendle, David; Shah, Uzma; Schwarzenberg, Sarah Jane; Pohl, John; Perito, Emily R.; Ooi, Chee Y.; Nathan, Jaimie D.; et al.
ABSTRACT: Objective: The aim of the study was to determine whether clinical characteristics and management of pediatric acute recurrent pancreatitis (ARP) and chronic pancreatitis (CP) differ across INSPPIRE (INternational Study Group of Pediatric Pancreatitis: In Search for a cuRE) sites. Study Design: Data were collected from INSPPIRE and analyzed per US regions and "non-US" sites. Between-group differences were compared by Pearson chi-square test. Differences in disease burden were compared by Kruskal-Wallis test. Results: Out of the 479 subjects, 121 (25%) were enrolled in West, 151 (32%) Midwest, 45 Northeast (9%), 78 (16%) South, and 84 (18%) at non-US sites. Hispanic ethnicity was more common in South ( P < 0.0001); white race in Northeast ( P = 0.009). CP was less common and time from diagnosis of first acute pancreatitis to CP was longer in children at non-US sites ( P = 0.0002 and P = 0.011, respectively). Genetic mutations were most common among all groups; PRSS1 variants predominated in Midwest ( P = 0.002). Gallstones were more frequent in South ( P = 0.002). Endoscopic retrograde cholangiopancreatography (ERCP) and computed tomography (CT) imaging were more commonly utilized in United States compared with non-United States ( P < 0.0001), but there were no differences in the use of MRI/MRCP. Disease burden was highest in the West and Midwest, possibly as total pancreatectomy and islet autotransplantation (TPIAT) referral sites were located in these regions. All therapies were less commonly administered in non-US sites ( P < 0.0001). Conclusions: This is the first study to describe geographical variations in the INSPPIRE cohort, which possibly reflect variations in practice and referral patterns. The underlying reason behind the lower frequency of CP and fewer treatments in non-United States sites need to be further explored. Abstract : Supplemental Digital Content is available in the text